2016
DOI: 10.1088/1367-2630/18/10/103042
|View full text |Cite
|
Sign up to set email alerts
|

Topologically protected loop flows in high voltage AC power grids

Abstract: Geographical features such as mountain ranges or big lakes and inland seas often result in large closed loops in high voltage AC power grids. Sizable circulating power flows have been recorded around such loops, which take up transmission line capacity and dissipate but do not deliver electric power. Power flows in high voltage AC transmission grids are dominantly governed by voltage angle differences between connected buses, much in the same way as Josephson currents depend on phase differences between tunnel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…[34] is the first paper to rigorously study multistability and establish that the active power flow equations have multistable solutions on a 6-node cycle network with balanced power injections. Several papers [10,14,32] have investigated mechanisms that create large loop flows and have shown that loop flows will persist even when the network returns to its normal operating condition. In [10], the basins of attraction for loop flows has been studied using Lyapunov theory.…”
Section: Loop Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] is the first paper to rigorously study multistability and establish that the active power flow equations have multistable solutions on a 6-node cycle network with balanced power injections. Several papers [10,14,32] have investigated mechanisms that create large loop flows and have shown that loop flows will persist even when the network returns to its normal operating condition. In [10], the basins of attraction for loop flows has been studied using Lyapunov theory.…”
Section: Loop Flowsmentioning
confidence: 99%
“…In some cases, changes in the distribution of power injections (and withdrawals) across the network cause the stable operating point to change. In other cases, it result from changes in network topology-either when a line trips, destroying a cycle; or when a previously open line is closed, creating a new cycle [10].…”
Section: Introductionmentioning
confidence: 99%
“…It proves that voltage dynamics should be taken into account in model of synchronous machines. In mountain ranges, big lakes or inland seas we often observe large closed loops in high voltage AC power grids [17]. The basins stability method has been used to identify three mechanisms which create the circulating power flows.…”
Section: Applicationsmentioning
confidence: 99%
“…The latter explicitly takes into account that power grids -and thus reasonable parametrizations of the KM + -exhibit multistability. In fact, the phase space can be populated by multiple desired synchronized states [21,22] representing different operating modes as well as several undesired non-synchronized states representing power outages [18,23,24,25]. In a recent study [26], we contributed to the field of multistability-based stability analyses by determining the minimal fatal shock in a Kuramoto-like representation of the British power grid (figure 1(a)).…”
Section: Introductionmentioning
confidence: 99%